The Influence of Environmental Social Governance, Firm Size, and Profitability on Firm Value - Rama, Mayliesya Hielmy Duisyah; Paramita, Veronika Santi (Moneta : Journal of Economics and Finance, 2025)
Global warming has grown significantly in importance as a critical environmental issue in recent years. This trend presents a considerable challenge for businesses. In an effort to increase awareness of sustainability, the Indonesia Stock Exchange launched the SRI-KEHATI Index, a stock index that includes companies that meet ESG criteria. Between 2019 and 2023, the worth of companies included in the index has shown a declining trend. This study examines the relationship of firm value with ESG, firm size, and profitability using secondary data from sustainability reports and financial statements. This study uses a quantitative approach that combines descriptive and causal methodologies. The study’s population is 43 companies, a selection of 11 companies was made as samples through purposive sampling techniques. The analysis technique applied is panel data regression. In conclusion, firm value is negatively affected by ESG, although firm size does not have an impact. ROA positively impacts firm value.